Tingkat Kesadaran terhadap Resiko Kanker Payudara pada Mahasiswa: Level of Awareness of Breast Cancer Risk in College Students - Devia Putri Lenggogeni; Hema Malini; Hacidira Vichalova; Bobby Febri Krisdianto (Fakultas Keperawatan Universitas Andalas, 2023)
Increasing awareness of breast cancer risk requires knowledge to identify risk factors, symptoms, attitudes, and behaviors for conducting breast screening. However, the facts showed that most female students from non-medical university students had not had adequate awareness of breast cancer prevention. This study aimed to investigate breast cancer awareness among female non-medical university students. This study used quantitative design with cross-sectional design. A sampling technique used a non-probability sampling technique which conducted to 370 non-medical students. A modified Breast Cancers Awareness Scale (BCAS-1) questionnaire was used to measure level awareness of students regarding risk factors of breast cancer. The results showed that most respondents were 19 years old (51.4%) and most respondents (69.2%) have a moderate level of awareness. The level of awareness has five domains, all of respondents which are mostly moderate: knowledge about risk factors (72.4%); signs of breast cancer (54.6%); attitudes toward breast cancer prevention (71.1%); barriers to screening (70.5%), and behaviours related to breast cancer awareness (66.5%). This study concluded that non-medical students had moderate knowledge, so it is recommended a health promotion and special training to perform breast self-examination regularly for university students, especially non-medical students.